Dental implants and osteonecrosis of maxilaries associated with biphosphonate: an integrative review (Research, Society and Development, 2020)
The great advancement of implantology in the last 50 years has led to a great demand for oral rehabilitation, however, a great number of prescriptions of antireabsorption drugs, such as bisphosphonate, have been observed, which are related to adverse effects such as osteonecrosis. This integrative review aims to evaluate the adverse effects of oral rehabilitation with dental implants in patients undergoing therapy with bisphosphonate. We investigated studies that included the period from 2008 to 2018, in the following PubMed, Scienc Direct and Biblioteca virtual em saúde. A total of 193 articles on the subject were found, after the application of the inclusion and exclusion criteria and the removal of the duplicates, the review had 8 articles for analysis. With a total sample of 805 patients and 705 implants placed, we had a rate of osteonecrosis in 10.18% of the patients, of which 82.92% were females and a developmental preference was observed in the mandible. With these results we can observe that there is an adverse effect on the rehabilitation with dental implants in these patients, being necessary an individual evaluation for the prevention of cases of osteonecrosis.